Does correctional education matter? Perspectives of prisoners at a male adult maximum-security prison in Zambia - Paul Kakupa (Elsevier, 2021)
It is widely believed that correctional education programs can significantly reduce crime and recidivism rates by rehabilitating prisoners into productive and law-abiding citizens. Several studies on correctional education focus on statistically measuring the impact of correctional education programs on recidivism and employment rates among ex-prisoners. However, little is known about how prisoners themselves perceive and experience such programs during incarceration. This qualitative study drew on empowerment theory constructs to explore correctional education experiences of ten male adult prisoners serving long jail sentences at a maximum security prison in Zambia. The analysis revealed the following: (i) correctional education is perceived as meaningful and relevant to inmates’ post-release employment needs; (ii) despite the transformation of prisons into correctional centers, correctional facilities are still characterized by coercive and oppressive practices that impinge on the effective delivery of correctional education; and (iii) correctional education, as currently provided, emphasizes economic objectives and neglects inmates’ broader rehabilitation needs. The implication is that correctional education may not be fully rehabilitative. It is recommended that the structure and delivery of these education programs should incorporate processes that offer a holistic remodeling of offenders’ behaviors.